2017
DOI: 10.3389/fmicb.2017.00177
|View full text |Cite
|
Sign up to set email alerts
|

Below-Background Ionizing Radiation as an Environmental Cue for Bacteria

Abstract: All organisms on earth grow under the influence of a natural and relatively constant dose of ionizing radiation referred to as background radiation, and so cells have different mechanisms to prevent the accumulation of damage caused by its different components. However, current knowledge of the deleterious effects of radiation on cells is based on the exposure to acute and high or to chronic, above background doses of radiation and therefore is not appropriate to explain the cellular and biochemical mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 32 publications
0
37
0
Order By: Relevance
“…All living organisms on earth are exposed to a relatively constant dose of ionizing radiation called natural background radiation (76)(77)(78). Due to the shielding effect of overburden, the underground space environment, especially the deep underground, exists in a state of low background radiation (79).…”
Section: Underground Low Background Radiation Environment and Oxidatimentioning
confidence: 99%
“…All living organisms on earth are exposed to a relatively constant dose of ionizing radiation called natural background radiation (76)(77)(78). Due to the shielding effect of overburden, the underground space environment, especially the deep underground, exists in a state of low background radiation (79).…”
Section: Underground Low Background Radiation Environment and Oxidatimentioning
confidence: 99%
“…Cells have evolved mechanisms for rapidly adjusting their biochemistry in response to changes in the environment, including radiation [22]. Most research has focused on the deleterious effects of acute, high or chronic radiation on cells, while some studies have demonstrated a stress response in cells grown at radiation doses that are 10 to 79 times lower than background [3]. In the present study, V79 cells cultured for 2 days in below-background radiation showed a changed protein profile.…”
Section: Discussionmentioning
confidence: 59%
“…Several researchers have investigated the effects of low background radiation on living organisms maintained in deep underground laboratories (DUGLs) [3,4]. Eugster observed that the cyanobacterium Mastigogladus laminosus cultured in the Simplon tunnel (2000 m of rock cover) died after a few weeks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A minimum amount of radiation exposure appears to be essential for living organisms to develop and function. [6][7][8][9][10] Hence, if one were to plot radiation dose from acute and protracted exposure vs dose response, where we reduce the radiation dose to begin at absolute zero, i.e. with no dose from ambient natural background radiation, one then arrives at a curve like the one in Figure 2, where there are 2 thresholds.…”
Section: The Double Thresholdmentioning
confidence: 99%